Pembuatan Dress Korset Cheongsam Era Renaissance Dengan Aplikasi Bordir 3D - Bilqis, Jihan; Arifiana, Deny (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Cheongsam is a traditional Chinese garment also known as qipao. The purpose of this research is to describe the process of creating a Renaissance-era cheongsam corset dress with 3D embroidery application and to describe the final result of the Renaissance-era cheongsam corset dress with 3D application. The research method used is the creative work method, which includes pre-design, design, realization, and presentation. In the pre-design stage, the source of inspiration used is the traditional Chinese garment, the cheongsam, combined with Renaissance corset design. The main fabric used is duchess satin, with tricot used as interlining to provide stability to the corset. In the realization stage, the design of the cheongsam corset dress is implemented into a fashion piece through processes such as measurement taking, pattern making, fabric cutting, and sewing. The garment is adorned with 3D embroidery application and sequins. The presentation stage is conducted through a seminar, describing the process of creation and the final result of the Renaissance-era cheongsam corset dress. The result of this research is a Renaissance-era cheongsam corset dress with 3D embroidery application that combines traditional Chinese design with Renaissance corset design. This research contributes to the development of cheongsam fashion design through the application of 3D embroidery technique.